2017
DOI: 10.1099/ijsem.0.002295
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas tarimensis sp. nov., an endophytic bacteria isolated from Populus euphratica

Abstract: An endophytic bacterium, MA-69, was isolated from the storage liquid in the stems of Populuseuphratica trees at the ancient Ugan River in Xinjiang, PR China. Strain MA-69 was found to be short rod-shaped, Gram-stain-negative, non-spore-forming, aerobic and motile by means of a monopolar flagellum. According to phylogenetic analysis based on 16S rRNA gene sequences, strain MA-69 was assigned to the genus Pseudomonas with highest 16S rRNA gene sequence similarity of 97.5 % to Pseudomonas azotifigens JCM 12708, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…nov. is similar to that of members of the P. stutzeri group [40, 41]. Major fatty acids include C 12 : 0 , C 16 : 0 , C 17 : 0 cyclo, C 19 : 0 cyclo ω8c and summed features 3 (C 16 : 1 ω6c and/or C 16 : 1 ω7c) and 8 (C 18 : 1 ω7c and/or C 18 : 1 ω6c).…”
Section: Phenotypic and Chemotaxonomic Characterisationmentioning
confidence: 86%
“…nov. is similar to that of members of the P. stutzeri group [40, 41]. Major fatty acids include C 12 : 0 , C 16 : 0 , C 17 : 0 cyclo, C 19 : 0 cyclo ω8c and summed features 3 (C 16 : 1 ω6c and/or C 16 : 1 ω7c) and 8 (C 18 : 1 ω7c and/or C 18 : 1 ω6c).…”
Section: Phenotypic and Chemotaxonomic Characterisationmentioning
confidence: 86%
“…Furthermore, we propose that S. kunmingensis is a later heterotypic synonym of S. chloritidismutans . The genome of P. tarimensis has not been sequenced yet, but a multilocus sequence analysis demonstrated that this species belongs to the P. stutzeri phylogenetic group, close to S. balearica and S. azotifigens [ 27 ]. The species proposed to be transferred to the genus Stutzerimonas are summarized in Table 6 .…”
Section: Taxonomic Conclusionmentioning
confidence: 99%
“…At the time of writing, over 250 species of Pseudomonas have been added to the list of validly published names (http://www.bacterio.net). Members of Pseudomonas are aerobic, Gram-negative, non-spore-forming, catalase- and oxidase-positive and have one or more polar flagella for motility [2]. Several species of Pseudomonas cause opportunistic infections in fish, including Pseudomonas anguilliseptica , P.…”
Section: Full-textmentioning
confidence: 99%